Hubungan Derajat Disabilitas terhadap Kualitas Hidup Pasien Pasca Stroke di Puskesmas Kedungmundu Semarang - Anggun Puspita Anggreini; Sri Puguh Kristiyawati; Novi Heri Yono (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
A clot or bleeding in the brain causes a stroke or a cerebral vascular disease that damages the nervous system. Patients suffering from strokes may have physical, mental, sensory, and intellectual disabilities that impede their interaction with the environment and prevent them from performing daily activities and quality of life. This research determines the correlation between the disability level and the quality of life of patients suffering from stroke treated at the Kedungmundu Public Healt Care. The quatitative research applied a cross sectional approach and collected the samples from 67 respondents using proposive sampling. The applied measuring tools were mRS and SSQOL. The Spearmen Rank statistical test obtained a p-value of 0,000. The result accepts Ha, indicating a significant correlation between the disability level and the quality of life of the post-stroke patient with a value of r = -0,542. The value indicates a moderate and negative correlation between the level of disability and the life quality of post-stroke patients. The research result suggest the implementation of the intervention to lower the disability level because it influences post-stroke patients with low quality life.